PERLINDUNGAN DAN KEDUDUKAN KORBAN DALAM TINDAK KEKERASAN DALAM RUMAH TANGGA MENURUT UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA DI INDONESIA - Faisal Khadafi (Jurnal Pembaharuan Hukum, 2016)
Law No. 23 of 2004 on the Elimination of Domestic Violence has the aim to prevent and cope with their acts of domestic violence and in law enforcement efforts as well as the principles contained in Law No. 23 of 2004 on the Elimination Domestic violence, namely respect for human rights, justice, and gender equality, non-discrimination, and protection of victims. The enactment of Law No. 23 of 2004 on the Elimination of Domestic Violence, has had an impact extensively on legal protection for victims of violence within families and households in particular, and in society in general.